2015
DOI: 10.7224/1537-2073.2013-045
|View full text |Cite
|
Sign up to set email alerts
|

Development and Effectiveness of a Psychoeducational Wellness Program for People with Multiple Sclerosis

Abstract: Background: Multiple sclerosis (MS) mostly affects young and middle-aged adults and is known to be associated with a host of factors involved in overall quality of life and well-being. The biopsychosocial model of disease takes into account the multifaceted nature of chronic illness and is commonly applied to MS. The present investigation examined the effectiveness of a 10-week psychoeducational MS wellness program that was developed on the basis of the biopsychosocial model and a wellness approach to treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…This damage can interfere with nervous system ability for communication and cause several physical signs and symptoms (Comptson & Coles 2008). The prevalence of the disease was 400000 in the United States and about 2 million in the world according to the National MS Society (Mcguire et al 2015;Pagnini et al 2014). In 2010, in Iran MS prevalence ranged from 5.3 to 74.28 per 100000 people in different regions (Hemmati Maslakpak & Raiesi 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This damage can interfere with nervous system ability for communication and cause several physical signs and symptoms (Comptson & Coles 2008). The prevalence of the disease was 400000 in the United States and about 2 million in the world according to the National MS Society (Mcguire et al 2015;Pagnini et al 2014). In 2010, in Iran MS prevalence ranged from 5.3 to 74.28 per 100000 people in different regions (Hemmati Maslakpak & Raiesi 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Two studies examined the effect of time-limited wellness programming on the physical functioning and psychosocial well-being of participants after ten to twelve weeks, and found improvements in depression, anxiety, perceived stress, pain, physical functioning and psychosocial well-being. 11,16 A third study examined outcomes after one year for newly enrolled MSADP participants and compared them to outcomes for wait-listed individuals with MS. In that study, MSADP participants reported less fatigue and decreased symptom frequency in comparison to the wait-listed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National MS Society, 400,000 people in the USA and about 2 million people worldwide suffer from MS [2, 3]. In 2010, 5.3 to 74.28 per 100,000 people in different areas suffered from MS in Iran [4].…”
Section: Introductionmentioning
confidence: 99%